Community-based pandemic preparedness: COVID-19 procedures of a Manitoba First Nation community - Grace Kyoon-Achan; Lynda Write (Journal of Community Safety and Well-Being, 2020)
The COVID-19 pandemic has impacted the Canadian health, social and economic landscape beginning early in 2020. Efforts to stem the viral tide have called into cooperation international, federal, and provincial governments. These governments are drawing on public health and socio-economic measures to prevent outbreaks in some cases and reduce infections and death rates in others. First Nations are a seemingly peripheral part of the general response, with communities being served by Indigenous Services Canada, a federal government institution responsible for First Nations health care. A participant observation process enabled the reporting of the community’s steps in pandemic planning and preparation. We showcase the work being accomplished on the ground in Nisichawayasihk Cree Nation, a community in northern Manitoba. This includes strong local leadership, evidence-based planning and decision-making, pooling and coordinating resources, ongoing communication, traditional medicines and health approaches, planning for mental health supports, ensuring food security and general safety for community members. All levels of community-based leadership along with strong, measured and well-coordinated action are required to prevent the outbreak of viral infections in First Nation communities.